SeeingVR: A Set of Tools to Make Virtual Reality More Accessible to People with Low Vision - Zhao, Yuhang; Cutrell, Ed; Holz, Christian; Morris, Meredith Ringel; Ofek, Eyal; Wilson, Andy (CHI 2019, 2019)
Current virtual reality applications do not support people who have low vision, i.e., vision loss that falls short of complete blindness but is not correctable by glasses. We present SeeingVR, a set of 14 tools that enhance a VR application for people with low vision by providing visual and audio augmentations. A user can select, adjust, and combine different tools based on their preferences. Nine of our tools modify an existing VR application post hoc via a plugin without developer effort. The rest require simple inputs from developers using a Unity toolkit we created that allows integrating all 14 of our low vision support tools during development. Our evaluation with 11 participants with low vision showed that SeeingVR enabled users to better enjoy VR and complete tasks more quickly and accurately. Developers also found our Unity toolkit easy and convenient to use.